Adopting an Abandoned Farm - Sanborn, Kate, 1839-1917 (Salt Lake City, UT : Project Gutenberg, 2004)
"Adopting an Abandoned Farm" by Kate Sanborn is a memoir written in the late 19th century. The book chronicles the author's experience as she transitions from urban life in New York to the rustic environment of a run-down farm in Gooseville, Connecticut. Sanborn explores her delight in the farming life, facing the challenges and rewards of rejuvenating a neglected property while capturing the charm of country life. The opening of the memoir introduces the reader to Sanborn's decision to leave the hustle and bustle of city life and embrace farming. She recounts her initial visit to Gooseville, where she discovers an old farmhouse for rent and is captivated by its potential. As she describes the cozy rooms and the sprawling land, she expresses her aspirations for the farm, revealing her heartfelt enthusiasm. The narrative hints at her future adventures and mishaps in managing a farm, from furnishing the house through local auctions to facing the practical realities of rural living, all delivered with a humorous and reflective tone. (This is an automatically generated summary.)
Release date is 2004-04-01
Steven desJardins and Distributed Proofreaders
Keywords: Farm life -- Fiction